Implementation of the Legal Value of Bhinci-Bhinciki Coolies of The Sultanate of Buton in The Maintenance of Government - Faharudin, Faharudin (SASI, 2022)
Introduction: Recognition of the existence of customary law in Indonesia has existed since the time of the independence of the Republic of Indonesia, which until now has been formally recognized by amendments to the 1945 Constitution of the Republic of Indonesia. This is expressly regulated in Article 18B paragraph (1 ) and paragraph (2) of the 1945 Constitution of the Republic of Indonesia.Purposes of the Research: To find out how far the Implementation of Constitutional Law Values of the Dignity of the Seven Buton Sultanates in the Implementation of Government.Methods of the Research: This type of research uses an empirical juridical type, with historical, conceptual and statutory approaches. Data is a collection of information needed in the implementation of a research that comes from various sources. Data obtained from the field both primary and secondary data were analyzed using qualitative analysis techniques, then presented in a descriptive form.Results of the Research: The legal values of Bhinci-bhinciki Coolies in the Baubau City Government include a culture of shame (pomae-maeaka), meaning that they are ashamed to do disgraceful things such as KKN, a culture of caring for each other (popia-piara), a culture of mutual love (poma-maasiaka), and culture of mutual respect (poangka-angkataka), so as to create a harmonious, safe, peaceful and peaceful atmosphere. Teachers value their students, parents love their children, and leaders value their subordinates. Subordinates who excel are given gifts/rewards such as salary increases and regular attention to promotion. Conversely, subordinates who violate are given sanctions/punishment.